View Single Post
Jan10-12, 11:21 PM
P: 10
how do you use the change of variable:
[itex]\xi[/itex] = x - ct

on the PDE
ut + c ux = 0

where u(t,x) = v(t,x-ct) = v(t,[itex]\xi[/itex])

to get

vt = 0

I am trying to follow the steps of Peter J. Olver in this document starting on pg 4 but get stuck here...i think i am missing an important calculus concept but cannot figure out what. He says to use the chain rule but i cannot figure out how that helps.

Any help GREATLY appreciated
Phys.Org News Partner Science news on
'Smart material' chin strap harvests energy from chewing
King Richard III died painfully on battlefield
Capturing ancient Maya sites from both a rat's and a 'bat's eye view'